Investigating Recovery Strategies to Optimize Performance and Well-being in Basketball - Marco Pernigoni (Baltic Journal of Sport and Health Sciences)
Background and objectives: The intense nature of basketball has been shown to generate substantial fatigue, leading to significant impairment in measures of performance, physiological status, and perceived well-being, which may persist in the days following exercise (Chatzinikolaou et al., 2014; Doma et al., 2018; Moreira et al., 2018; Pliauga et al., 2015). Therefore, the use of recovery strategies aimed at minimizing these negative effects is essential (Davis et al., 2022), especially considering the increasing occurrence of congested match schedules in basketball (Pernigoni et al., 2024). Specifically, the aim of this dissertation was to investigate the effectiveness of recovery strategies which have received limited attention across basketball-specific research.